2016
DOI: 10.1007/s00198-016-3846-6
|View full text |Cite|
|
Sign up to set email alerts
|

Compressive loading of the murine tibia reveals site-specific micro-scale differences in adaptation and maturation rates of bone

Abstract: SummaryLoading increases bone mass and strength in a site-specific manner; however, possible effects of loading on bone matrix composition have not been evaluated. Site-specific structural and material properties of mouse bone were analyzed on the macro- and micro/molecular scale in the presence and absence of axial loading. The response of bone to load is heterogeneous, adapting at molecular, micro-, and macro-levels.IntroductionOsteoporosis is a degenerative disease resulting in reduced bone mineral density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…In addition to altering bone mass and microstructure, some studies have indicated that mechanical loading can also alter bone mineral and matrix properties . The material bone mineral density or so‐called tissue mineral density (TMD) represents a volume of bone matrix that does not include marrow spaces, osteonal canals, lacunae or canaliculi, thus reflecting the degree of mineralization of organic bone matrix.…”
Section: Outcome Measures To Consider For Tibial Loading Studies and mentioning
confidence: 99%
“…In addition to altering bone mass and microstructure, some studies have indicated that mechanical loading can also alter bone mineral and matrix properties . The material bone mineral density or so‐called tissue mineral density (TMD) represents a volume of bone matrix that does not include marrow spaces, osteonal canals, lacunae or canaliculi, thus reflecting the degree of mineralization of organic bone matrix.…”
Section: Outcome Measures To Consider For Tibial Loading Studies and mentioning
confidence: 99%
“…Mechanical loading causes a rapid anabolic response in specific regions of the periosteum [3][4][5][6]. However, the origin of the cells that contribute to new osteoblast formation in this setting is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…The bone anabolic response to loading is site-specific, where most bone formation is seen at the periosteal caudal site [3,26]. Therefore, we investigated the number of osteoblasts and their origin at the periosteal caudal site and compared it to the cranial surface where less bone is formed in response to load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations